2017
DOI: 10.1139/cjz-2016-0242
|View full text |Cite
|
Sign up to set email alerts
|

Nest cover and faecal glucocorticoid metabolites are linked to hatching success and telomere length in breeding Common Eiders (Somateria mollissima)

Abstract: Habitat-associated crypsis may affect perceived predation vulnerability, selecting for different predator avoidance strategies. Glucocorticoids could mediate the adjustment of escape responses to the extent of crypsis, introducing an overlooked source of variation in glucocorticoid–fitness relationships. However, prolonged exposure to elevated glucocorticoids may be costly, leading to accelerated telomere loss and, consequently, senescence. Here, we examined how nest cover and immunoreactive faecal glucocortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 89 publications
(137 reference statements)
0
7
0
Order By: Relevance
“…[49] Similarly, perceived predation risk (degree of nest crypsis) affected telomere length in hatching common eiders (Somateria mollissima), in which chicks hatching from uncovered nests have shorter telomeres. [50] The telomere-messenger hypothesis provides an adaptive explanation for these results. Hence, under high predation pressures, shorter telomeres would favor a fast pace-of life strategy and an increased investment in reproduction.…”
Section: A New Hypothesis: the Telomere Messenger Hypothesismentioning
confidence: 99%
“…[49] Similarly, perceived predation risk (degree of nest crypsis) affected telomere length in hatching common eiders (Somateria mollissima), in which chicks hatching from uncovered nests have shorter telomeres. [50] The telomere-messenger hypothesis provides an adaptive explanation for these results. Hence, under high predation pressures, shorter telomeres would favor a fast pace-of life strategy and an increased investment in reproduction.…”
Section: A New Hypothesis: the Telomere Messenger Hypothesismentioning
confidence: 99%
“…Every plate also included serial doubling dilutions of a standard sample, which was later used to construct standard curves. Further details on the application of the telomere assay to the current study population can be found elsewhere (Noreikiene et al 2017). The mean qPCR efficiencies as determined by the standard curves for telomere and gapdh reactions fell within the acceptable range of 85-115% (Bize et al 2009).…”
Section: Telomere Assaymentioning
confidence: 86%
“…However, extreme caution needs to be exercised when attempting to draw parallels to our present study. This is because the RTL of adult female eiders shows no significant trend with age (Noreikiene et al 2017), and female age was not associated with offspring RTL (Table 2). Clearly, there is a need for further longitudinal analysis of the covariation between maternal and offspring RTL over the lifespan of females.…”
Section: Offspring Rtlmentioning
confidence: 95%
See 1 more Smart Citation
“…Telomere length may represent a complimentary measure of RRV. Thus, although the telomere length of adult female Eiders is not significantly associated with age or body condition, reproductive success may be achieved at the expense of telomere length (Noreikiene et al 2017). Female reproductive success was measured as proportional hatching success.…”
Section: Introductionmentioning
confidence: 99%